Competitive activity analysis of young sportsmen in ball hockey - Klyuchnikova, S. N.; Malofeev, A. Y.; Nemytov, D. N. (The Russian Journal of Physical Education and Sport, 2016)
Annotation. Technical-tactical actions of the players form a central part of a competitive game and a training practice, which demand a lot of time for their improvement in the process of a long-term sports training. The system of sports training management provides a complex pedagogical control, which helps to determine quantitative and qualitative sides of motional activity among young sportsmen. In particular, control and further indices analysis of the playing competitive activity helps to estimate a young hockey players` readiness and brings necessary corrections into the training process. Research methods: scientific and methodical literature analysis and summarizing, pedagogical observation, competitive activity indices registration, statistical analysis. Materials. The article is about competitive activity of young hockey players of the secondary school age, different All-Russian tournaments participants, in particular, the effectiveness of technical-tactical actions among 13-15 year-old hockey players during the competitive period is revealed. Results. Actual statistical results of the official games in ball hockey for children and teen-agers helped to fulfill the analysis of competitive activity effectiveness according to the parameters of technical-tactical actions (TTA) effectiveness. Technical-tactical indices of competitive activity among young hockey players helped to reveal their changes in age-related aspect. Conclusion. A rational planning of educational-training process during year-round and a long-term training gives a necessary effect only if there is pedagogical control system over it. The results of the research help to optimize the content of sports training in ball hockey, substantiate new approaches to testing exercises choice (pedagogical control means) concerning the normative demands of the curriculum at sports school for children and teen-agers (sports schools of the Olympic reserve for children and teen-agers) fulfillment according to its main units (physical training, technical-tactical training).